2020
DOI: 10.14789/jmj.2020.66.jmj19-oa23
|View full text |Cite
|
Sign up to set email alerts
|

Status of Normal Weight Obesity Among Japanese Women Under 40 Years Old

Abstract: This study examined the prevalence of and factors affecting normal weight obesity (NWO) among women aged under 40 years old. NWO was having a normal BMI but a high body-fat percentage (BFP). Materials and Methods: We recruited 399 participants aged 1839 during a health checkup and surveyed them about lifestyle patterns, height, weight, body composition, and girth and visceral fat area. Participants were divided into three. Those with a BMI of < 25 and a BFP of < 30 were classified as non-obese, a BMI of < 25 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Thus, it is suggested that the decrease in muscle mass, associated with the problems of body composition, is observed earlier in the lower limbs than in the upper limbs. Previous studies also reported that gait speed was significantly positively correlated with SMI among young women [ 10 ], and it was a predictor of NWO among participants aged 20–29 [ 28 ]. Therefore, the current PAL among female students especially affects the lower limb muscle mass, and it may cause difficulty in independent mobility in the younger generation, even in those who had an exercise habituation in the past.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, it is suggested that the decrease in muscle mass, associated with the problems of body composition, is observed earlier in the lower limbs than in the upper limbs. Previous studies also reported that gait speed was significantly positively correlated with SMI among young women [ 10 ], and it was a predictor of NWO among participants aged 20–29 [ 28 ]. Therefore, the current PAL among female students especially affects the lower limb muscle mass, and it may cause difficulty in independent mobility in the younger generation, even in those who had an exercise habituation in the past.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, normal weight obesity (NWO), which means that the body weight is normal; however, the body fat is high, which is considered an issue of body composition. NWO individuals were associated with a significantly lower AMM when compared with non-obese individuals in their thirties [ 28 ]. However, such a significantly lower AMM in individuals with NWO in their twenties and aged 18–19 years was observed only in the lower limbs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, stabilizing the standing posture and preventing impaired walking function lead to preventive care [ 6 , 7 ]. However, young women have problems with “thinness” accompanied by muscle loss and atrophy, and “hidden obesity” with normal BMI and low lean mass [ 8 , 9 ]. The presence of muscle atrophy (sarcopenia) has been reported in women in their 20s.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that a high PAL as well as total energy intake and protein intake among the three macronutrients are contributed with high muscle mass and muscle strength in young females. こと (Hayashi et al, 2006;Sugawara et al, 2009)や正常体重肥満など身体組成に関する 問題 (Fukuoka et al, 2012;Nakanishi et al, 2020)…”
mentioning
confidence: 99%